2017
DOI: 10.1002/bio.3429
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance liquid chromatography study of gatifloxacin and sparfloxacin using erythrosine as post‐column resonance Rayleigh scattering reagent and mechanism study

Abstract: Herein, a highly selective high-performance liquid chromatography (HPLC) coupled with resonance Rayleigh scattering (RRS) method was developed to detect gatifloxacin (GFLX) and sparfloxacin (SPLX). GFLX and SPLX were first separated by HPLC, then, in pH 4.4 Britton-Robinson (BR) buffer medium, protonic quaternary ammonia cation of GFLX and SPLX reacted with erythrosine (ERY) to form 1:1 ion-association complexes, which resulted in a significant enhancement of RRS signal. The experimental conditions of HPLC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…As in previous studies [24,25], the chromatograms of Xi Lei San and indirubin were confirmed by HPLC. Xi Lei San and indirubin solutions were prepared and analyzed by HPLC performed using a Hypersil NH2 column (250 mm × 4:6 mm, 5 mm).…”
Section: High-performance Liquid Chromatography (Hplc)supporting
confidence: 81%
“…As in previous studies [24,25], the chromatograms of Xi Lei San and indirubin were confirmed by HPLC. Xi Lei San and indirubin solutions were prepared and analyzed by HPLC performed using a Hypersil NH2 column (250 mm × 4:6 mm, 5 mm).…”
Section: High-performance Liquid Chromatography (Hplc)supporting
confidence: 81%
“…This technique has been applied by the World Health Organization (WHO), the State Food and Drug Administration of China (SFDA) as a strategic plan for the quality assessment of TCM [9,10], and got increasing concerns because it focuses on the characterization of the total sample composition. Several ways, for instance, high-performance thin layer chromatography (HPTLC) [11][12][13][14], thin-layer chromatography (TLC) [15][16][17], infrared spectroscopy (IR) [18][19][20], mass spectrometry (MS) [21,22], gas chromatography (GC) [23,24], high-performance liquid chromatography (HPLC) [25][26][27], nuclear magnetic resonance (NMR) [28][29][30][31] and high-performance liquid chromatography (UPLC) [32][33][34] are utilized for fingerprinting to characterize multiple compounds in the tested herbal samples. Among the abovementioned methods, HPLC is generally the most applied method for its high sensitivity, selectivity, and low cost [35].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the RRS method has been widely used for the determination of trace substances, for example, nucleic acids, [ 28 ] proteins, [ 29 ] inorganic ions, [ 30,31 ] organic compounds, [ 32,33 ] drugs, [ 34–36 ] etc. [ 37–39 ] Recent studies have shown that the RRS method can be also applied to the determination of antibiotics such as fluoroquinolones, [ 40,41 ] cephalosporins, [ 42 ] tetracyclines, [ 43 ] macrolides, [ 44 ] aminoglycosides, [ 45 ] etc. In the past few years, there have been reports on the quantitative analysis of NEO using the RRS method.…”
Section: Introductionmentioning
confidence: 99%